Development of Socio-Emotional and Creative Skills in Primary Education: Teachers' Perceptions About the Gulbenkian XXI School Learning Communities Project - Cristóvão, Ana M.; Candeias, Adelinda A.; Verdasca, José Lopes (Frontiers in Education, 2020)
In recent decades, several authors have warned of the need to equip students with skills that include critical thinking, creativity, and emotional management. Emotions can facilitate or impede children’s academic engagement, commitment, and ultimate school success since relationships and emotional processes affect how and what we learn. Teachers are the main emotional leaders of their students, and the foundation for promoting emotional balance within their groups is their ability to recognize, understand, and manage their emotions. The SEL approach defends that, as with academic skills, the development of social and emotional skills must be accomplished through explicit instruction. In the academic year 2014/2015, three schools in the Portuguese region of the Alentejo began an innovative four-year project to promote change in learning. The main goal was to improve learning by promoting the acquisition of basic knowledge within the formal curriculum and to stimulate the development of analytical and practical reasoning skills, resilience and responsibility, as well as technological, emotional, social and creative skills. To this end, the research team created two programs to be developed in primary school, the Emotional Literacy Program (ELP) and the Creative Thinking Development Program (Flow) as well as a training program for teachers, Mediators for Well- Being Program. This article details a study analyzing the perceptions of primary school teachers who participated in the project. Data were collected by interviews and teachers’ reflections were analyzed. Content analysis was chosen as the analytical technique as it is appropriate for treating qualitative data. The results show very positive impacts on the professional and personal development of teachers. Teachers reported improvements in student behavior, in the relationships between them and in the classroom environment. They further emphasized the need for teachers to receive more training in emotional education in their academic and in service education.